Kearbitreran Bahasa Arab dan Urgensi Mempelajarinya dalam Pandangan Linguis Arab Klasik - Fathi Hidayah (Universitas Yudharta Pasuruan, 2019)
Arabic is one of the most complicated languages ​​in terms of grammar. The difference in the mention of verbs for each subject gives philosophically hidden meanings. The uniqueness of the Arabic language is much described by classical scholars, who of course cannot be separated from its philosophy. Not only mention Arabic as the language of heaven, but there are many descriptions about it. These classical scholars in the book Abu Mansur Ats-tsa'laby, who mention the virtues of Arabic are Umar bin Khatab, Imam Shafi'i, Al-Jahiz to Ibn Junni. In addition, Arabic lexicologists also gave their descriptions of the virtues of the Arabic language.